Blockage of transient receptor potential vanilloid 4 inhibits brain edema in middle cerebral artery occlusion mice - Jie, Pinghui; Tian, Yujing; Hong, Zhiwen; Li, Lin; Zhou, Libin; Chen, Lei; Chen, Ling (Frontiers in Cellular Neuroscience, 2015)
Brain edema is an important pathological process during stroke. Activation of transient receptor potential vanilloid 4 (TRPV4) causes an up-regulation of matrix metalloproteinases (MMPs) in lung tissue. MMP can digest the endothelial basal lamina to destroy blood brain barrier, leading to vasogenic brain edema. Herein, we tested whether TRPV4-blockage could inhibit brain edema through inhibiting MMPs in middle cerebral artery occlusion (MCAO) mice. We found that the brain water content and Evans blue extravasation at 48 h post-MCAO were reduced by a TRPV4 antagonist HC-067047. The increased MMP-2/9 protein in hippocampus of MCAO mice was attenuated by HC-067046, but only the increased MMP-9 activity was blocked by HC-067047. The loss of zonula occluden-1 (ZO-1) and occludin protein in MCAO mice was also attenuated by HC-067047. Moreover, MMP-2/9 protein increased in mice treated with a TRPV4 agonist GSK1016790A, but only MMP-9 activity was increased by GSK1016790A. Finally, ZO-1 and occludin protein was decreased by GSK1016790A, which was reversed by an MMP-9 inhibitor. We conclude that blockage of TRPV4 may inhibit brain edema in cerebral ischemia through inhibiting MMP-9 activation and the loss of tight junction protein.